MODERN SOCIO-DEMOGRAPHIC TRENDS AFFECTING THE BUSINESS SECTOR OF THE ECONOMIES OF LATVIA AND UKRAINE - Mietule, Iveta; Maksymova, Iryna; Holikova, Kateryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper analyses and describes key social and demographic trends affecting the business in current conditions. The present research aims to establish logical coherence and feedback between economic development and basic socio-demographic indicators in European countries, including the experience of Latvia and Ukraine. The challenge of the research leads to answering the question how demographic processes affect and drive the economy and how this mechanism could be used to predict essential trends of future development. The methodology of cluster analysis, statistical and regression methods were employed for modelling. Cluster analysis was applied to depict an economic cartogram and merge some European countries in particular clusters by current socio-demographic and economic criteria. As a result, this approach allowed us to compare Latvia and Ukraine as highlighting representatives of different economic clusters and distinguish important similarities and differences. Statistical data were based on the following indicators: GDP, income, employment, age structure, gender, population aging, location, migration etc. These parameters were analysed due to their dynamic change. Regression methods allowed to establish the whole system of indicators affecting the business environment in Latvia and Ukraine. For instance, the results confirmed the explicit impact of migration trends on business and social development.